REABILITAÇÃO PULMONAR COM TREINAMENTO DE EQUILÍBRIO EM PACIENTES COM DOENÇA PULMONAR OBSTRUTIVA CRÔNICA: UMA REVISÃO SISTEMÁTICA - dos Santos, Tamires Daros (2020)
The objective of this study was to systematically review the literature on the efficacy of adding balance training (BT) into pulmonary rehabilitation (PR) programs, in comparison to conventional PR to improve postural balance in individuals with chronic obstructive pulmonary disease (COPD). The search strategy was applied in the PubMed/MEDLINE, SciELO, LILACS, PEDro, Scopus and Web of Science databases, with no restriction as regards the year of publication or language, according to the PRISMA recommendations. Inclusion criteria were: clinical trials involving BT in PR to improve postural balance in subjects with COPD, published up to June 2019. Two reviewers selected the studies, extracted the data and assessed the risk of bias, using Cochrane’s Handbook, independently. Of the 172 potentially eligible studies, 2 were included, with a total of 107 patients with COPD, of whom 56 were allocated in the intervention group (BT additionally to conventional PR) and the others in the control group (conventional PR). Balance training additionally to PR provided an improvement in postural balance in relation to conventional PR, however no significant differences were found between the groups regarding the level of confidence in performing specific activities and tolerance to the exercise. The studies presented a low risk of bias (high quality). These findings suggest that the addition of BT into conventional PR programs is more effective to improve postural balance in comparison to conventional PR. However, given the low number of studies available, there is no robust evidence to support clinical decision making.